1992
DOI: 10.1002/cjce.5450700213
|View full text |Cite
|
Sign up to set email alerts
|

The behavior of ethylene glycol during the thermal solvolysis of cellulose

Abstract: The composition of the ethylene glycol solution resulting from cellulose thermal solvolysis, to produce microcrystal‐line cellulose, has been studied. Liquid and gas chromatographic analyses showed, a) little degradation of the ethylene glycol up to 280°C, and b) an acceleration of the degradation at higher temperatures in the presence of cellulose and glucose. Solubilized compounds resulting from the cellulose depolymerization although numerous were present in too low concentrations to warrant their recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Compounds in the latter category were assumed to be degraded from lignocellulosic components, among which PAME was dominant. 3-(2-Methyl-1,3-dioxolan-2-yl) propanoic acid methyl ester was detected in the thermal solvolysis products of cellulose (Vidal et al 1992). Zhang et al (2012) reported 3-(2-methyl-1,3-dioxolan-2-yl) propanoic acid ethyl ester in the liquefied compounds from acid hydrolysis residue of corncob in EG.…”
Section: Characterization Of Liquefied Products With Gc-msmentioning
confidence: 99%
“…Compounds in the latter category were assumed to be degraded from lignocellulosic components, among which PAME was dominant. 3-(2-Methyl-1,3-dioxolan-2-yl) propanoic acid methyl ester was detected in the thermal solvolysis products of cellulose (Vidal et al 1992). Zhang et al (2012) reported 3-(2-methyl-1,3-dioxolan-2-yl) propanoic acid ethyl ester in the liquefied compounds from acid hydrolysis residue of corncob in EG.…”
Section: Characterization Of Liquefied Products With Gc-msmentioning
confidence: 99%